2012
DOI: 10.1590/s1808-18512012000100001
|View full text |Cite
|
Sign up to set email alerts
|

Influência da extensão da artrodese lombossacra nos resultados clínicos e funcionais

Abstract: RESUMOObjetivo: Verificar a influência da extensão da fusão póstero-lateral lombossacra e seu impacto nos resultados clínicos e funcionais. Métodos: Foram avaliados 22 pacientes portadores de estenose central, foraminal ou hérnia de disco lombar, associadas a instabilidade segmentar, submetidos ao tratamento cirúrgico para a descompressão neural e artrodese póstero-lateral. Os pacientes foram divididos em dois grupos, de acordo com quantidade de níveis artrodesados: Grupo 1: fusão em um nível e Grupo 2: fusão … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…We observed, in the patients studied, a significant improvement in the different aspects of quality of life after surgery, 6 with the exception of the areas of physical limitation and social aspects. Our results are similar to those of Gotfryd et al 18 who demonstrated that 22 patients who underwent lumbar arthrodesis presented good levels of quality of life, with the exception of the domain physical limitation.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We observed, in the patients studied, a significant improvement in the different aspects of quality of life after surgery, 6 with the exception of the areas of physical limitation and social aspects. Our results are similar to those of Gotfryd et al 18 who demonstrated that 22 patients who underwent lumbar arthrodesis presented good levels of quality of life, with the exception of the domain physical limitation.…”
Section: Resultssupporting
confidence: 92%
“…On the other hand, after analysis of 30 patients with failure of conservative treatment and indication for surgery, Oliveira et al, in 2014, obtained a mean PI of 45° that is below the average for the asymptomatic population. [16][17][18] The Oswestry scale (Oswestry Disability Index -ODI) is an instrument for assessing the quality of life in disorders of the column by means of 10 clinical criteria with 6 answer alternatives each. It is used to access the degree of incapacity and the result after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with the results in the literature, we believe that a precise indication is fundamentally important to favorable results in the surgical treatment of this condition. The studies by Glassman et al, 25 Valesin Filho et al, 17 and Godfryd et al 26 observed a statistical difference in the quality of life in relation to the number of arthrodesed levels. In view of this, we can conclude that when well-indicated, surgical treatment may present favorable results regardless of the scope of the surgery, although there is no consensus around this subject in the literature.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to the criteria of Linovitz et al, 9 we used the criteria proposed by Christensen et al 13 in a complementary and subjective way, to classify the consolidation rate and the fusion grade. Besides its low cost, non-invasive surgery provides uniformity and high intra-and inter-evaluator reliability (93% and 86%, respectively) 14 when compared to the "gold standard" for checking the fusion mass by surgical exploration.…”
Section: Resultsmentioning
confidence: 99%